Peak Oil - Bennett, David (New Zealand Science Review, 2012)
​‘Peak Oil’, and the entire subject of oil economics and supply and demand would only be lightly scratched by an entire semester of lectures; so what I have to say here is of necessity very summary. Oil is a valuable substance. But at US100 per barrel, crude oil is still only 1/30 the price of beer for the same volume. Even at the petrol pump, petrol is still only one-tenth of the price of beer at the tap. Yet the production and delivery of the food we eat, the clothes we wear and the articles we use in our normal life are heavily dependant on the continuing supply of oil and gas. So it is rational to consider how certain the continuation of this supply is.